2017
DOI: 10.1002/2017gl074231
|View full text |Cite
|
Sign up to set email alerts
|

Advance, Retreat, and Halt of Abrupt Gravel‐Sand Transitions in Alluvial Rivers

Abstract: Downstream fining of bed sediment in alluvial rivers is usually gradual, but often an abrupt decrease in characteristic grain size occurs from about 10 to 1 mm, i.e., a gravel‐sand transition (GST) or gravel front. Here we present an analytical model of GST migration that explicitly accounts for gravel and sand transport and deposition in the gravel reach, sea level change, subsidence, and delta progradation. The model shows that even a limited gravel supply to a sand bed reach induces progradation of a gravel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 37 publications
2
52
0
1
Order By: Relevance
“…Yet if the controls change so slowly that the stream can keep pace with them, the stream continuously finds itself in a state of quasi‐equilibrium, in which the proposed formulations can be applied. This is illustrated by Blom et al [] for the case of an abrupt gravel‐sand transition.…”
Section: Discussionmentioning
confidence: 91%
“…Yet if the controls change so slowly that the stream can keep pace with them, the stream continuously finds itself in a state of quasi‐equilibrium, in which the proposed formulations can be applied. This is illustrated by Blom et al [] for the case of an abrupt gravel‐sand transition.…”
Section: Discussionmentioning
confidence: 91%
“…The channel response timescale or system relaxation time reflects how fast a reach responds (with respect to channel slope, channel width, and the bed surface texture) to changes in the controls (Blom et al, ; De Vries, ; Howard, ). As the channel response timescale is generally long, there exists a subset of relatively short‐term control changes that do not appreciably affect the equilibrium state.…”
Section: Introductionmentioning
confidence: 99%
“…This implies that short‐term periodicity in controls produces negligible to limited associated channel response (e.g., Chatanantavet & Lamb, ; Howard, ; Viparelli et al, ). On the contrary, if the channel response timescale is much shorter than the timescale of changes of the controls (e.g., for slow control changes or in a small, highly mobile reach), channel geometry keeps pace with the changing controls (i.e., a quasi‐equilibrium state; Figure c; Blom, Chavarrías, et al, ; Howard, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examination of gravel-sand transitions along downstream river profiles indicates that the mode of bed-material transport may switch abruptly from near threshold (gravel bedded) to suspension (sand bedded) (Miller et al, 2014;Venditti et al, 2015Venditti et al, , 2010Singer, 2010Singer, , 2008Blom et al, 2017), and hydraulic considerations have suggested that susceptibility to suspension increases rapidly as grain size decreases across the gravel to sand range (Lamb and Venditti, 2016). On the other hand, recent compilations of global datasets have been used to suggest that rivers exhibit a continuum of transport states -from near threshold through to full suspension -and that bank-full Shields stress varies smoothly with grain size, slope, and particle Reynolds number (Parker et al, 2007;Wilkerson and Parker, 2010;Li et al, 2015;Trampush et al, 2014)).…”
Section: Introductionmentioning
confidence: 99%